Evaluation of gene markers invA, phsB, and tviA for detection of Salmonella Typhi by SYBR Green TM real-time PCR assay in clinical samples - Muhammad Luqman Qadir; Samreen Arshad; Nazim Hussain; Saima Younas; Rabia Arooj; Ahmer Bin Hafeez (Molecular Biology Reports, 2026)

Curcuma caesia-derived carbon quantum dots: Green synthesis, biocompatibility, pharmacological and anti-counterfeiting applications - Sanjana bai Shivaram singh Mahendranath singh; Sushma Mohan; Shivakumar Venkataramaiah; Manjula Mavathur Venkatappa; Vani Karadi Manjappa; Rajesh Rangappa; Bethuru Rangaswamy Radha Krushna; Idagur Somashekar Pruthviraj; Hanumanthappa Nagabhushana; Hosam O. Elansary; Ihab Mohamed Moussa; Muhammad nazim; et al. (Toxicon, 2026)

Mechanistic Insights into Silicon-Induced Modulation of Morphophysiological Traits and Plant Defense System in Mung Bean (Vigna Radiata L.) under Drought Stress - Mazhar Abbas; Ejaz Ahmad Waraich; Muhammad Ahmad; Nazia Ishfaq; Arslan Haider; Tahrim Ramzan; Muhammad Nazim; Usman Zulfiqar; Muhammad Faisal Maqsood; Abdul Rehman; Waleed A. A. Alsakkaf; Hayssam M. Ali (Journal of Soil Science and Plant Nutrition, 2026)

Stem Cells and their Key Derivatives in Degenerative Musculoskeletal Diseases - Nawaz Khan; Zeynab Ahmadova; Bin Zeng; Waqas Ahmed; Tayyab Shafiq; Zihao Zhang; Aiyuan Su; Nazim Muhammad; Sajid Khan; Yujie Liang; Li Duan (Stem Cell Reviews and Reports, 2026)

Molecular insights into HPV-16 L2 capsid protein and inhibitor screening study - Saima Younas; Atiqa Nosheen; Muhammad Abdul Qayyum; Hafiza Ayesha Malik; Sadia Manzoor; Rabia Arooj; Nazim Hussain; Qurban Ali; Muhammad Arshad Javed; Daoud Ali; Adnan Iqbal (In Silico Pharmacology, 2026)

Nano-silicon-induced modulation of heavy metal metabolism in plants: pathways to climate-resilient phytoremediation - Muhammad Nazim; Abida Hussain; Aamir Nawaz; Shazia Anjum; Muqarrab Ali; Xiangyi Li (Nanotechnology for Environmental Engineering, 2026)

Potassium Silicate-Induced Nitrogen Assimilation and Osmoregulation in Cotton Leaves Under Deficit Irrigation - Muhammad Nazim; Xiangyi Li; Khurram Shahzad; Zhang Dawei; Fanjiang Zeng (Journal of Soil Science and Plant Nutrition, 2026)

Plant-derived biostimulants: Emerging trends, breakthroughs and challenges in 2024 - Qurat Ul Ain Hyder; Abida Aziz; Muhammad Farooq Azhar; Muhammad Hasnain Haider; Nazim Hussain (Organic Agriculture, 2026)

Moringa oleifera: a comprehensive review with special emphasis on phytochemistry - Muhammad Nazim; Wajid Raza; Faiz ul Hassan Nasim; Shazia Anjum; Hammad Ullah; Asif Nawaz; Muhammad Ayaz; Maria Daglia (Phytochemistry Reviews, 2026)

Mitigating cadmium-stressed spinach by the synergistic effect of vermicompost and selenium: associated heath risks assessment - Taiba Rauf; Kamran Ashraf; Zeeshan Ahmed; Rabiya Nasir; Muhammad Zeeshan Mansha; Qamar uz Zaman; Ghulam Murtaza; M. Ajmal Ali; Mohamed S. Elshikh; Rashid Iqbal; Lala Gurbanova; Nazim S. Gruda (Environmental Geochemistry and Health, 2026)

Retraction notice to “Citric acid-capped NiWO4/Bi2S3 and rGO-doped NiWO4/Bi2S3 nanoarchitectures for photocatalytic decontamination of emerging pollutants from the aqueous environment” [Environ. Res. Volume 212, Part B, September 2022, 113276] - Hina Liaquat; Muhammad Imran; Shoomaila Latif; Sajid Iqbal; Nazim Hussain; Muhammad Bilal (Environmental Research, 2025)

Retraction notice to “Development of reduced graphene oxide-supported novel hybrid nanomaterials (Bi2WO6@rGO and Cu-WO4@rGO) for green and efficient oxidative desulfurization of model fuel oil for environmental depollution” [Environ. Res., Part A, 212 (2022), 113160] - Aqsa Riaz; Muhammad Saeed; Mamoona Munir; Azeem Intisar; Sabah Haider; Shahzaib Tariq; Nazim Hussain; Rehana Kousar; Muhammad Bilal (Environmental Research, 2025)

Synergistic Role of Gibberellic acid, Cytokinin and Zinc Application in Enhancing Nutrient Accumulation and Grain Quality of Rice (Oryza Sativa L.) - Ravneet Kaur; Muhammad Nazim; Bhupendra Mathpal (Journal of Soil Science and Plant Nutrition, 2025)

Unveiling the Potential of Garcinia Atroviridis Root-Derived Phenolic Compounds Against Breast Cancer: Isolation, Network Pharmacology and In-Silico Approaches - Nur Salsabila Binti Ahmad Roslan; Miah Roney; Abdul Rashid Issahaku; Md. Nazim Uddin; Mohd Fadhlizil Fasihi Mohd Aluwi; Seema Zareen; Anke Wilhelm; Ahmad Mahfuz Gazali; Muhammad Nadeem Akhtar; Normaiza Binti Zamri (Journal of Pharmaceutical Innovation, 2025)

Corrigendum to “Application of nanomaterials for enhanced production of biodiesel, biooil, biogas, bioethanol, and biohydrogen via lignocellulosic biomass transformation” [Fuel 315 (2022) 122840] - Mehvish Mumtaz; Zulqarnain Baqar; Nazim Hussain; Afifa; Muhammad Bilal; Hafiz Muhammad Husnain Azam; Qurat-ul-ain Baqir; Hafiz M.N. Iqbal (Fuel, 2025)

Moringa Bio-stimulator with Soil Organic Nitrogen Ameliorated Nitrogen Use Efficiency and Drought Tolerance for Healthy Proso-millet Production - Muhammad Maqsood; Nazim Hussain; Azra Yasmeen; Hamid Nawaz (Journal of Crop Health, 2025)

Multivariate analysis of potential health hazards of manganese via dietary exposure of widely consumed vegetables amended with municipal solid waste - Asma Ashfaq; Zafar Iqbal Khan; Kafeel Ahmad; Hamid Raza; Muhammad Nazim; Ajaz Ahmad (Environmental Geochemistry and Health, 2025)

Multivariate Statistical Evaluation of 20 Metals/Metalloid Levels in the Serum of Patients with Prostate Gland Diseases - Muhammad Abdul Qayyum; Mian H. R. Mahmood; Tahir Farooq; Ahmad Irfan; Shahid Iqbal; Nazim Hussain (Indian Journal of Clinical Biochemistry, 2025)

Alleviating cadmium-induced stress in maize: the role of zinc sulphate application on growth and biochemical responses - Sadaf Saeed; Awais Manzoor; Arslan Haider; Tahrim Ramzan; Hafeez ur Rehman; Muhammad Ahmad; Shahzad Bashir; Usman Zulfiqar; Muhammad Nazim; Muhammad Faisal Maqsood; Waleed A. A. Alsakkaf; Hayssam M. Ali (Environmental Science and Pollution Research, 2025)

Heavy Metal Uptake by Spirogyra splendida and Spirogyra circumlineata: A Sustainable Approach to Industrial Wastewater Remediation - Sadam Khan; Yuanren Jiang; Siqi Shen; Muhammad Riaz; Muhammad Tariq; Zhenxin Li; Rafiq Ahmad; Sidra Sohail; Nazim Hassan (Water, Air, & Soil Pollution, 2025)

Significance of Selenium in Improving the Yield and Quality of Quinoa Under Drought - Muhammad Usman Aslam; Muhammad Aown Sammar Raza; Rashid Iqbal; Salman Ahmad; Imran Haider; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Saltanat Aghayeva; Nazim S. Gruda (Journal of Soil Science and Plant Nutrition, 2025)

Moringa Biopriming with Zn Spray Improved Nutrients Rich Biofortified Chickpea Grains and Drought Tolerance at Reproductive Stages Under Arid Environment - Hamid Nawaz; Malik Muhammad Yousaf; Nazim Hussain; Tanveer Hussain; Malik Waqar Yousaf; Malik Ibrar Yousaf; Mona S. Alwahibi; Mohamed S. Elshikh; Baber Ali; Rashid Iqbal (Journal of Crop Health, 2025)

Exogenous Potassium Silicate Improves Drought Tolerance in Cotton Genotypes by Modulating Growth, Gas Exchange and Antioxidant Metabolism - Muhammad Nazim; Xiangyi Li; Akash Tariq; Khurram Shahzad; Murad Muhammad; Zhang Dawei; Fanjiang Zeng (Journal of Crop Health, 2024)

Air pollution and climate change as grand challenges to sustainability - Afifa; Kashaf Arshad; Nazim Hussain; Muhammad Hamza Ashraf; Muhammad Zafar Saleem (Science of The Total Environment, 2024)

Silicon nanoparticles: A novel approach in plant physiology to combat drought stress in arid environment - Muhammad Nazim; Xiangyi Li; Shazia Anjum; Fiaz Ahmad; Muqarrab Ali; Murad Muhammad; Khurram Shahzad; Lisha Lin; Usman Zulfiqar (Biocatalysis and Agricultural Biotechnology, 2024)

Heteroatom-doped MXenes as electrocatalysts for hydrogen evolution reaction: A review on the recent advances, mechanisms and prospects - Abdul Hanan; Muhammad Nazim Lakhan; Rashmi Walvekar; Mohammad Khalid; Chander Prakash (Chemical Engineering Journal, 2024)

MOFs coupled transition metals, graphene, and MXenes: Emerging electrocatalysts for hydrogen evolution reaction - Abdul Hanan; Muhammad Nazim Lakhan; Faiza Bibi; Amjad Khan; Irfan Ali Soomro; Altaf Hussain; Umair Aftab (Chemical Engineering Journal, 2024)

Reflectance spectra for identifying stress in different parts of leaf: a case study on oil palm seedlings - Muna E. Raypah; Muhammad Imran Mohd Nasru; Muhammad Hazeem Hasnol Nazim; Ahmad Fairuz Omar; Jelena Muncan; Siti Anis Dalila Muhammad Zahir; Mohd Faizal Jamlos; Haider Mahmod Jasim (International Journal of Remote Sensing, 2024)

An insights into emerging trends to control the threats of antimicrobial resistance (AMR): an address to public health risks - Ayesha Asghar; Aneeza Khalid; Zulqarnain Baqar; Nazim Hussain; Muhammad Zafar Saleem; Sairash; Komal Rizwan (Archives of Microbiology, 2024)

Comparative Analysis of IgG Antibody Titers Induced by Three Different SARS-COV-2 Vaccines in Healthy Adults of Pakistan - Nayab Batool Rizvi; Hassam Farooq; Qaiser Alam Khan; Muhammad Zeeshan Rana; Sehrish Zaffar; Muhammad Shahid; Nazim Hussain (Current Microbiology, 2023)

Adsorptive and photocatalytic degradation potential of porous polymeric materials for removal of pesticides, pharmaceuticals, and dyes-based emerging contaminants from water - Azeem Intisar; Arooj Ramzan; Shahzar Hafeez; Nazim Hussain; Muhammad Irfan; Nasir Shakeel; Komal Aziz Gill; Amjad Iqbal; Marcin Janczarek; Teofil Jesionowski (Chemosphere, 2023)

Transforming Lignin Biomass to Value: Interplay Between Ligninolytic Enzymes and Lignocellulose Depolymerization - Namra Ahmad; Shakira Aslam; Nazim Hussain; Muhammad Bilal; Hafiz M. N. Iqbal (BioEnergy Research, 2023)
Lignin is the main constituent of lignocellulosic biomasses, which have a significant untapped ability to replace ecologically unfavorable and non-renewable fossil fuels. The lignin is broken down by ligninolytic bacteria, which also use a peripheral pathway to transform heterogeneous lignin derivatives into central intermediates like protocatechuate or catechol. By undergoing ring cleavage through the -ketoadipate pathway, these intermediates become metabolites by producing acetyl-CoA for internal product biosynthesis, including the creation of triacylglycerols and polyhydroxyalkanoates. Expanding our understanding of ligninolytic microbial communities, strains, and enzymes through bioprospecting can help us better understand the metabolism of aromatics. The most viable idea for sustainable development is the valorization of lignin into biopolymers as well as other high-value goods. This process is now being used to generate a variety of biopolymers, including polyesters, epoxies, phenol resins, poly (lactic acids), poly hydroxyl alkanoates, and polyurethanes. Furthermore, lignin recalcitrance remained a possible barrier to efficient lignin valorization, prompting several efforts to design high-efficiency bioprocesses to produce specific polymer types as well as other important bioproducts. Graphical Abstract

Taurine protected Trifolium alexandrinum L. plants from damages of individual and interactive effects of chromium and drought stress - Muhammad Arslan Ashraf; Rizwan Rasheed; Iqbal Hussain; Mudassir Iqbal Shad; Wajeeha Nazim (Acta Physiologiae Plantarum, 2023)

Multifunctional catalyst-assisted sustainable reformation of lignocellulosic biomass into environmentally friendly biofuel and value-added chemicals - Muhammad Naeem; Muhammad Imran; Shoomaila Latif; Adnan Ashraf; Nazim Hussain; Grzegorz Boczkaj; Wojciech Smułek; Teofil Jesionowski; Muhammad Bilal (Chemosphere, 2023)

Moringa oleifera leaf extract mediated green synthesis of silver nanoparticles and their antibacterial effect against selected gram-negative strains - Mehwish Younas; Muhammad Hidayat Rasool; Mohsin Khurshid; Amjad Khan; Muhammad Zeshan Nawaz; Ijaz Ahmad; Muhammad Nazim Lakhan (Biochemical Systematics and Ecology, 2023)

Development of zinc ferrite nanoparticles with enhanced photocatalytic performance for remediation of environmentally toxic pharmaceutical waste diclofenac sodium from wastewater - Shoomaila Latif; Amna Liaqat; Muhammad Imran; Ayesha Javaid; Nazim Hussain; Teofil Jesionowski; Muhammad Bilal (Environmental Research, 2023)

Novel strategies and advancement in reducing heavy metals from the contaminated environment - Quratulain Maqsood; Nazim Hussain; Mehvish Mumtaz; Muhammad Bilal; Hafiz M. N. Iqbal (Archives of Microbiology, 2022)

Tocopherol as plant protector: an overview of Tocopherol biosynthesis enzymes and their role as antioxidant and signaling molecules - Essa Ali; Sayed Hussain; Nazim Hussain; Kaleem Ullah Kakar; Jawad Munawar Shah; Syed Hassan Raza Zaidi; Masood Jan; Kewei Zhang; Muhammad Ali Khan; Muhammad Imtiaz (Acta Physiologiae Plantarum, 2022)

Deciphering the impact of novel coronavirus pandemic on agricultural sustainability, food security, and socio-economic sectors—a review - Mehvish Mumtaz; Nazim Hussain; Zulqarnain Baqar; Saima Anwar; Muhammad Bilal (Environmental Science and Pollution Research, 2021)

Isolation and functional characterization of exopolysaccharide produced by Lactobacillus plantarum S123 isolated from traditional Chinese cheese - Muhammad Saleem; Samiullah Malik; Hafiza Mahreen Mehwish; Muhammad Waqas Ali; Nazim Hussain; Mohsin Khurshid; Muhammad Shahid Riaz Rajoka; Yougen Chen (Archives of Microbiology, 2021)

Expression profiling of miRNA-196a biomarker in naïve hepatitis C virus-infected and Sofosbuvir plus Daclatasvir-treated patients - Nazim Hussain; Nimrah Farooq; Muhammad Maqsood; Muhammad Shahid Riaz Rajoka; Muhammad Bilal (Archives of Microbiology, 2021)

Correction to: Characterization, the Antioxidant and Antimicrobial Activity of Exopolysaccharide Isolated from Poultry Origin Lactobacilli - Muhammad Shahid Riaz Rajoka; Hafiza Mahreen Mehwish; Hafiz Fakhar Hayat; Nazim Hussain; Sobia Sarwar; Humaira Aslam; Ahmad Nadeem; Junling Shi (Probiotics and Antimicrobial Proteins, 2019)

Characterization, the Antioxidant and Antimicrobial Activity of Exopolysaccharide Isolated from Poultry Origin Lactobacilli - Muhammad Shahid Riaz Rajoka; Hafiza Mahreen Mehwish; Hafiz Fakhar Hayat; Nazim Hussain; Sobia Sarwar; Humaira Aslam; Ahmad Nadeem; Junling Shi (Probiotics and Antimicrobial Proteins, 2019)